2018
DOI: 10.1371/journal.pone.0201162
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and premotor activity during a non-fatiguing grip task reflects motor fatigue in relapsing-remitting multiple sclerosis

Abstract: Fatigue is a common and highly disabling symptom of multiple sclerosis. Patients experience an effort-independent general subjective feeling of fatigue as well as excessive fatigability when engaging in physical or mental activity. Previous research using functional magnetic resonance imaging (fMRI) has revealed heterogeneous findings, but some evidence implicates the motor system. To identify brain correlates of fatigue, 44 mildly impaired patients with relapsing-remitting multiple sclerosis and 25 age- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…All participants had completed three testing days, including clinical assessments, structural and functional magnetic resonance imaging, and electroencephalography. These data are reported elsewhere (16).…”
Section: Subjectssupporting
confidence: 75%
See 2 more Smart Citations
“…All participants had completed three testing days, including clinical assessments, structural and functional magnetic resonance imaging, and electroencephalography. These data are reported elsewhere (16).…”
Section: Subjectssupporting
confidence: 75%
“…These studies revealed a reduction of pre-movement facilitation that correlated with individual fatigue scores (14,15), pointing to an impaired initialization of movements. Complementing these task-related TMS studies, task-related functional brain imaging studies found excessive recruitment of higher-order premotor areas, such as the dorsal premotor cortex (16)(17)(18). The premotor activity may reflect excessive volitional drive in the context of inefficient movement initiation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Motor regions were less deactivated and DMN areas were more deactivated in RRMS, but not in SPMS vs HC Pardini et al, 2013 14 people with RRMS Finger to thumb opposition with the right hand (index, medium, ring and little fingers) During the finger tapping task, temporal accuracy of task execution was higher in fatigued MS and correlated with higher cerebellar and orbitofrontal fMRI activity Faivre et al, 2015 13 people with RRMS 14 HC Auditory-cued flexion–extension of the fingers of one hand Compared to HC, people with MS presented higher fMRI activation during a motor task (especially when executed with non-dominant hand) and higher RS FC. Levels of hyper-activation and hyper-connectivity at RS were inter-related Rocca et al, 2016 79 people with MS 26 HC Flexion-extension of the last four fingers of the right, dominant hand Fatigued MS people showed reduced activation of sensorimotor, temporal and basal ganglia regions, and increased frontal activation compared to non-fatigued MS. Time-modulation analysis showed reduced fMRI activity over time in non-fatigued MS only Hubbard et al, 2016 25 people with RRMS 20 HC Press and release both thumb-buttons at presentation of a checkerboard stimulus Amplitude of the BOLD response in the visual and motor cortex was reduced in people with MS vs HC, and correlated with microstructural damage Bonzano et al, 2017 14 people with RRMS Finger to thumb opposition with the right hand (index, medium, ring and little fingers) fMRI activity in basal ganglia regions (known to be involved in fatigue) and amygdala was high during the non-demanding finger tapping task, decreased during the execution of the highly demanding finger tapping task, and returned to baseline after a resting period Tacchino et al, 2017 17 people with CIS 20 people with RRMS 20 HC Squeeze (and imagine to squeeze) a foam ball with the dominant and non-dominant hand Reduced performance of motor imagery varied according to disease stage (i.e., in CIS vs RRMS), and inversely associated with fMRI activations of occipital, frontal and parietal regions (which were stronger with the non-dominant hand) Svolgaard et al, 2018 44 people with RRMS 25 HC Press a pincer grip a force sensitive device, and produce a force matching that showed on a screen In people with MS, during the precision grip task, fMRI activity of the cerebellum was proportional to fatigue. Linear increase of activity over time in premotor and frontal regions was impaired in MS according to fatigue severity …”
Section: Using Fmri To Explore Ms-related Functional Reorganization W...mentioning
confidence: 99%
“…At day two, participants underwent a scan session including functional, structural, dMRI and quantitative MRI scans. Results from the functional MRI are reported in ( Svolgaard et al, 2018 ). All scan sessions were performed in the morning and within the same time frame for all subjects.…”
Section: Methodsmentioning
confidence: 99%